Preparation and Characterization of Nd3+:ZnO-B2O3-Al2O3-SiO2 Transparent Glass-Ceramics - Zou, Xiang-Yu; Zhang, Hong-Bo; Su, Chun-Hui (Asian Journal of Chemistry, 2013)
Nd3+-doped transparent ZnO-Al2O3-B2O3-SiO2 glass ceramics was prepared by controlled crystallization of melt-quenched glass. The glass-ceramics sample is characterized by DSC, XRD, SEM and photoluminescence spectra. We discussed the crystalline phase of glass-ceramic composition, crystal structure, microstructure morphology and the relationship of the heat-treatment to the optical transmittance and absorption lines, The fluorescence spectra of the glass-ceramics samples were studied and results showed that the neodymium ion doped glass-ceramics samples in the range of 850-1400 nm emission intensity is higher than the neodymium doped glass samples and glass to glass-ceramic conversion of the fluorescence properties of the neodymium ion enhance and different heat treatment. The fluorescence spectra were compared to identify the variation between the heat treatment temperature and the emission intensity.